2008
DOI: 10.1196/annals.1447.017
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ Plasmid Construction and Delivery for the Prevention of Type 1 Diabetes

Abstract: Studies of animals with spontaneous autoimmune diabetes have revealed that autoreactive T cells that mediate islet beta cell destruction can be manipulated by the administration of Th(2) cytokines. Using gene delivery to express the targeted protein, we can overcome the need for frequent administration of cytokines on account of their short half-lives. In this study, the effect of hTGFbeta gene delivery was evaluated both in vitro and in vivo using an adenovirus vector (Ad) constructed with an hTGFbeta cDNA. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have shown that TGF-β plays an important role in the development of autoimmune diabetes. 12,13 TGF-β plasmid injection delays the development of diabetes in NOD mice, 13 and TGF-β induces Foxp3 + T cells, restores self-tolerance and facilitates regeneration of beta-cell function in NOD mice, 27 suggesting that TGF-β plays a preventive role in the development of type 1 diabetes. TGF-β exerts biological functions through Smad-dependent and Smad-independent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that TGF-β plays an important role in the development of autoimmune diabetes. 12,13 TGF-β plasmid injection delays the development of diabetes in NOD mice, 13 and TGF-β induces Foxp3 + T cells, restores self-tolerance and facilitates regeneration of beta-cell function in NOD mice, 27 suggesting that TGF-β plays a preventive role in the development of type 1 diabetes. TGF-β exerts biological functions through Smad-dependent and Smad-independent signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of type 1 diabetes, TGF‐β suppresses the spontaneous onset of type 1 diabetes via expansion of Forkhead box (Fox)p3 + Treg cells within the islets of the pancreas 12 . TGF‐β also inhibits islet apoptosis and enhances proliferation and differentiation of Treg cells in non‐obese diabetic (NOD) mice 13 . In addition, serum TGF‐β levels in type 1 diabetic patients is lower than in healthy controls, 14 suggesting that TGF‐β might play a preventive role in the development of diabetes.…”
mentioning
confidence: 99%
“…Gene therapy has been used also to reduce migration of immune cells involved in the detrimental phase of the autoimmune disorders. Park et al studied the differential effects of the delivery of a dominant-negative variant of CCL2 (7ND) by gene therapy on acute, biphasic and chronic EAE: in acute EAE and in the first attack of biphasic EAE, this therapy, especially effective in inhibiting migration of macrophages, was most ineffective because pathogenic T cells are mainly involved in lesion formation; in contrast, during the relapse of biphasic EAE and during chronic EAE, macrophages play a major role in the disease process and 7ND delivery by gene therapy was more effective [29]. A similar strategy has been attempted by intramuscular administration of decoy chemokine receptors, i.e., plasmids encoding the binding sites of CXCR3 and CCR2.…”
Section: Decoy Receptorsmentioning
confidence: 96%